Analysis Of Factors Affecting Women Marriing Early In Jembrana District - Ayu Wulandari; Ida Ayu Nyoman Saskara (Pusat Riset dan Inovasi Nasional, 2024)
Fertility is influenced by the low age at first marriage, high population growth is a burden on national development, so efforts are needed to reduce the rate of population growth. Population growth in Jembrana Regency cannot be separated from fertility, because the low age at first marriage has an impact on early marriage which is triggered by factors such as the respondent's education, parents' education and income, premarital pregnancy and area of residence. This study aims to analyze the simultaneous and partial influence of respondents' education level, parents' education and income, premarital pregnancy, and area of residence on early marriage among women in Jembrana Regency. The number of samples in this study was 100 PUS women who were married and lived in Jembrana Regency. The sample determination method used was nonprobability sampling , namely Quota Sampling and Accidental Sampling . The data analysis technique used is logistic regression analysis. The results of this study show that, simultaneously, the respondent's education level, parents' education and income, premarital pregnancy, and area of residence have a significant effect on early marriage among women in Jembrana Regency. The respondent's education level, parents' education, namely the father, and parents' income partially have a negative and significant effect on early marriage among women in Jembrana Regency, while the respondent's mother's education does not have a negative and insignificant effect on early marriage among women in Jembrana Regency. Premarital pregnancy causes more early marriages compared to not premarital pregnancy and the difference is significant . Area of residence means that respondents who live in villages experience early marriage at a higher rate than those who live in cities and the difference is significant.